Active and placebo transcranial magnetic stimulation effects on external and internal auditory hallucinations of schizophrenia - Paillère Martinot, Marie-Laure; Galinowski, André; Andoh, Jamila (Acta psychiatrica Scandinavica, 2017)
Objective Repetitive transcranial magnetic stimulation (rTMS) over the left temporo-parietal region has been proposed as a treatment for resistant auditory verbal hallucinations (AVH), but which patients are more likely to benefit from rTMS is still unclear. This study sought to assess the effects of rTMS on AVH, with a focus on hallucination phenomenology. Method Twenty-seven patients with schizophrenia and medication-resistant AVH participated to a randomized, double-blind, placebo-controlled, add-on rTMS study. The stimulation targeted a language-perception area individually determined using functional magnetic resonance imaging and a language recognition task. AVH were assessed using the hallucination subscale of the Scale for the Assessment of Positive Symptoms (SAPS). The spatial location of AVH was assessed using the Psychotic Symptom Rating Scales. Results A significant improvement in SAPS hallucination subscale score was observed in both actively treated and placebo-treated groups with no difference between both modalities. Patients with external AVH were significantly more improved than patients with internal AVH, with both modalities. Conclusions A marked placebo effect of rTMS was observed in patients with resistant AVH. Patients with prominent external AVH may be more likely to benefit from both active and placebo interventions. Cortical effects related to non-magnetic stimulation of the auditory cortex are suggested.
Published online: 16 December 2016
Gesehen am 22.05.2018